Support for Adaptive and Distributed Deployment of CEP Continuous Queries for the IoMT - Magalhães, Fernando Benedito Veras; Silva, Francisco José da Silva e; Endler, Markus (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
The current dissemination of IoT increases the deployment of stream processing solutions for monitoring and controlling elements of the real-world. One of those solutions is Complex Event Processing (CEP), and to handle the high volume, velocity and volatility of data streams from IoT sensors the CEP pipeline should be distributed, preferably having CEP operators both in the cloud/cluster and in edge devices. In this paper, we present a model for a distributed CEP platform and an implementation of this model called Global CEP Manager (GCM). GCM is a service of the ContextNet middleware that supports the deployment and dynamic rearrangement of CEP queries to CEP engines executing in the cloud and in M-Hubs, that are ContextNet’s mobile edge devices.